Rates and predictors of child maltreatment re-perpetration against new victims and prior victims. (January 2022) - Potter, Marina Haddock; Kennedy, Reeve S.; Font, Sarah A.
Abstract: Background: Limited prior research has examined the rates or predictors of re-perpetration of child maltreatment. Yet, perpetrators may have multiple victims, and perpetrators, rather than their victims, are often the primary focus of child welfare services. Objective: We examine rates of child maltreatment re-perpetration of repeat and new victims, and test perpetrator demographics and maltreatment index incident case characteristics as predictors of re-perpetration. Participants and setting: We use a sample of 285, 245 first-time perpetrators of a substantiated maltreatment incident in 2010 from the National Child Abuse and Neglect Data System. Methods: We use linear probability models with full information maximum likelihood to test new victim and same victim perpetration by the end of FY 2018. Results: Fifteen percent of perpetrators re-maltreated one or more of their original victims ("same victim re-perpetration"); 12% maltreated a new victim. Overall, re-perpetration was more common among younger, female, and White perpetrators. Perpetrators who were the biological or adoptive parent of their initial victim(s) had higher rates of same victim re-perpetration; new victim re-perpetration was more common among perpetrators who initially victimized an adoptive or stepchild. Same victim re-perpetration was less common among perpetrators of physical abuse than other types of maltreatment, and new victim re-perpetration was more common among perpetrators of sexual abuse and neglect than physical abuse. Conclusions: Child welfare agencies should track re-perpetration in addition to revictimization as part of agency evaluations and risk assessments.